ASSOCIATION OF ABO AND RH BLOOD GROUPS WITH COVID-19 PCR POSITIVE STATUS: A CASE CONTROL STUDY - Asif, Shabana; Ahmed, Aashi; Batool, Aliya; Anwar, Bushra; Gul, Ambreen; Kayani, Muslim (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine association of ABO and Rh blood groups with COVID-19 RT-PCR positive status.Study Design: Case control study.Place and Duration of the Study: Department of Pathology, Margalla Hospital Taxila, from Apr 2020 to Dec 2020.Methodology: The sample comprised of 436 cases and 500 controls. Out of 3936 RT-PCR done during the study duration, 436 RT-PCR positives were enrolled in study as cases. 500 age and gender matched controls were selected from same population. Study variables (age, gender, blood groups, RT-PCR result) were obtained from Hospital data (HIMS). Data was analyzed using SPSS version 25. Mean and SD was calculated for age. Frequencies were calculated for categorical variables. p-value calculated applying chi square test. Odds ratios calculated to determine association.Results: The mean age of cases was 37.3 ± 16.3. Statistically significant association was observed between age, gender and COVID-19 RT-PCR positive status. B+ blood group was most frequent both among cases (35.4%) and controls (36.2%), followed by O+ and A+. However, no significant association was observed between blood groups and COVID-19 RTPCR positivity. Odds ratios calculated for blood group O and non - O (OR=0.95), A antigen (OR=0.97) and Rh factor (OR 0.93) among cases and controls showed week negative association. Whereas a weak positive association of B antigen + and B antigen - with PCR positivity (1.07) was observed between cases and controls.Conclusion: Susceptibility to acquire COVID-19 infection is not associated with ABO and Rh blood groups according to this study.